Are some athletes more cognitive skilled than others when choosing their opponents in skiing-sprint elimination tournaments? - Niklas Karlsson; Anders Lunander (Örebro University School of Business, 2022)
The study analyzes data from world cup cross-country skiing sprint elimination tournaments for men and women in 2015-2020. In these tournaments prequalified athletes sequentially choose in which of five quarterfinal heats they want to compete. Due to a time constraint on the day the tournament is held, the recovery time between the elimination heats varies. This implies a clear advantage for the athlete to race in an early rather than in a late quarterfinal to increase the chances of being successful in a possible final. Given that athletes seek to maximize their expected achieved world cup points when choosing quarterfinal, a simple model predicts that higher ranked athletes prefer to compete in early quarterfinals, despite facing expected harder competition. The result is consistent with our empirical analysis of the data. We also develop two estimation methods to investigate whether some athletes are found to be more tactical skilled in their decision making. Our estimates indicate that twelve out of 115 athletes have made choices having an expected positive effect on their performance in terms of achieved world cup points. For 22 athletes the effect is expected to be negative. The estimated individual effects ranges from -3 points to +4 points.
Keywords: C51; C72; D91; Z20; 330; elimination tournament; game theory; choosing opponents; skiing sprint; tactical skills